2012
DOI: 10.1016/j.molimm.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Two isoforms of anti-lipopolysaccharide factors identified and characterized from the hemocytes of portunid crabs, Portunus pelagicus and Scylla tranquebarica

Abstract: a b s t r a c tAnti-lipopolysaccharide factors (ALFs), a type of cationic antimicrobial peptides (AMPs), and their derivatives are becoming predominant candidates for potential drugs in viral and bacterial diseases. This study reports the first ALF from the mud crab Scylla tranquebarica (StALF, JQ899453) and the second ALF isoform from the blue swimmer crab Portunus pelagicus (PpALF2, JQ899452). Both sequences encoded for precursor molecules, starting with a signal peptide containing 26 amino acid residues, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Comparison of their sequences with those of previously characterized ALFs showed that both contain an LPS-binding domain [33]. The sequences of PpALF2 and StALF are rich in positively charged amino acid residues: both PpALF 2 and StALF contain 12.4% lysine (Lys) and also contain 5.2% and 6.2% arginine (Arg), respectively.…”
Section: Anti-lps Factorsmentioning
confidence: 99%
“…Comparison of their sequences with those of previously characterized ALFs showed that both contain an LPS-binding domain [33]. The sequences of PpALF2 and StALF are rich in positively charged amino acid residues: both PpALF 2 and StALF contain 12.4% lysine (Lys) and also contain 5.2% and 6.2% arginine (Arg), respectively.…”
Section: Anti-lps Factorsmentioning
confidence: 99%
“…ALF was first reported in chelicerates (horseshoe crab, Limulus polyphemus ) as a potent anticoagulant factor (Morita et al 1985 ; Ohashi et al 1984 ; Tanaka et al 1982 ). Since then, ALFs were identified in various crustaceans, such as portunid crabs (Afsal et al 2012 ), freshwater prawn (Ren et al 2012 ), crayfish (Jiravanichpaisal et al 2007 ; Sun et al 2011 ) and penaeid shrimp, such as Litopenaeus vannamei , Fenneropenaeus chinensis, Penaeus monodon and M . japonicus (Tassanakajon et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%